Case Report: Mycobacterial epidural pyogranulomatous steatitis in a cat - Decrop, Flora; Henriques, Tiago; Hermann, Annika; Fina, Caroline; Álvarez, Patricia; Mínguez, Juanjo; Posporis, Christoforos (Frontiers in Veterinary Science, 2025)
A 2-year-old neutered male domestic short-haired cat was presented with chronic spinal hyperesthesia and a 24-h acute progression to non-ambulatory, non-painful tetraparesis, consistent with a C1-T2 myelopathy. Physical examination, serum biochemistry, hematology, thoracic and abdominal imaging were unremarkable. Magnetic resonance imaging revealed a well-defined, crescent-shaped, extra-dural, compressive, T2w/T1w/STIR hyperintense contrast-enhancing mass lesion within the dorsal and right lateral vertebral canal, from C2 to cranial C4. Mild mononuclear pleocytosis and increased protein concentration were detected on CSF analysis. Serology for Feline Corona Virus (FeCoV), Toxoplasma gondii IgM and IgG, Cryptococcus antigen, FIV/FeLV and CSF PCR for T. gondii and FeCoV were negative. A right-sided C2-C3 hemilaminectomy was performed, and the mass was debulked. Histopathology showed marked pyogranulomatous steatitis with multifocal lymphofollicular hyperplasia. Ziehl-Neelsen and PAS stains, as well as immunohistochemistry for FeCoV were negative. Positive amplicons with the DNA sequence most closely related to the genus Mycobacterium were detected on hsp65 gene-targeted PCR and sequencing of the resected tissue. The cat was treated with a one-week course of prednisolone, and was prescribed a six-month course of clarithromycin, pradofloxacin, and rifampicin, with clarithromycin being discontinued after 35 days due to poor patient compliance. A rapid and complete recovery was confirmed on re-examination at 2 weeks and no recurrence was reported at last follow-up, 20 months after diagnosis. This case represents one of the first documented instances of focal mycobacterial epidural steatitis in a cat, underscoring the importance of considering Mycobacterium infection in the differential diagnosis of epidural pathology. It also emphasizes the utility of PCR and subsequent sequencing for precise diagnosis. With appropriate treatment, a favorable long-term outcome is achievable.